2022
DOI: 10.3233/jpd-212851
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian Randomisation Study of Smoking, Alcohol, and Coffee Drinking in Relation to Parkinson’s Disease

Abstract: Background: Previous studies showed that lifestyle behaviors (cigarette smoking, alcohol, coffee) are inversely associated with Parkinson’s disease (PD). The prodromal phase of PD raises the possibility that these associations may be explained by reverse causation. Objective: To examine associations of lifestyle behaviors with PD using two-sample Mendelian randomisation (MR) and the potential for survival and incidence-prevalence biases. Methods: We used summary statistics from publicly available studies to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…This also makes physiological sense, as those individuals who metabolize caffeine more slowly will tend to drink less coffee to achieve the same levels of plasma caffeine. A previous MR study found no association between genetically predicted coffee consumption and Parkinson's disease [20], which is in line with our overall null results for genetically predicted plasma caffeine levels and this disease.…”
Section: Discussionsupporting
confidence: 92%
“…This also makes physiological sense, as those individuals who metabolize caffeine more slowly will tend to drink less coffee to achieve the same levels of plasma caffeine. A previous MR study found no association between genetically predicted coffee consumption and Parkinson's disease [20], which is in line with our overall null results for genetically predicted plasma caffeine levels and this disease.…”
Section: Discussionsupporting
confidence: 92%
“…The fact that drugs used in nicotine dependence were inversely associated with PD in our study, even though these drugs are not used frequently, is a strong argument in favor of the validity of our PD case ascertainment method and ML‐based signal detection approach. The inverse association between smoking and PD is indeed one of the most consistent observations in PD epidemiology, 42 and recent Mendelian randomization studies support a causal association 43 . Because drugs for nicotine dependence were retained in the models, our analyses are indirectly and partially adjusted for smoking.…”
Section: Discussionmentioning
confidence: 64%
“…Recent MR studies showed an inverse association between genetically predicted smoking and PD 15‐18 . These findings are in favor of a causal role of smoking in PD, but the underlying mechanisms remain unknown and gene–environment interactions analyses may contribute to their understanding.…”
Section: Discussionmentioning
confidence: 92%
“…Recent MR studies showed an inverse association between genetically predicted smoking and PD. [15][16][17][18] These findings are in favor of a causal role of smoking in PD, but the underlying mechanisms remain unknown and gene-environment interactions analyses may contribute to their understanding. The interaction pattern we found is similar to the interaction between selfreported smoking and rs660895 reported by Chuang et al 7 Our study represents a fully independent replication using a different approach to define smoking (MR) and SNP-based imputation of HLA amino acids that allowed us to examine this interaction at the AA level.…”
Section: Discussionmentioning
confidence: 99%